2011
DOI: 10.1007/s11633-011-0578-0
|View full text |Cite
|
Sign up to set email alerts
|

Throughput analysis of the IEEE 802.11 distributed coordination function considering erroneous channel and capture effects

Abstract: This paper presents a performance study of the distributed coordination function (DCF) of 802.11 networks considering erroneous channel and capture effects under non-saturated traffic conditions employing a basic access method. The aggregate throughput of a practical wireless local area network (WLAN) strongly depends on the channel conditions. In a real radio environment, the received signal power at the access point from a station is subjected to deterministic path loss, shadowing, and fast multipath fading.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…For example, in [6], authors performed experiments and showed that there exists capture effect on wireless interfaces. Moreover in [12][13][14], authors proposed models for the performance analysis of IEEE 802.11 WLAN in the presence of capture effect.…”
Section: Related Workmentioning
confidence: 99%
“…For example, in [6], authors performed experiments and showed that there exists capture effect on wireless interfaces. Moreover in [12][13][14], authors proposed models for the performance analysis of IEEE 802.11 WLAN in the presence of capture effect.…”
Section: Related Workmentioning
confidence: 99%
“…Some 9 to 37 nodes are used within four mobility groups indoor on AODV and OLSR protocols, and it is found that the approach of choreographing node movement is suitable for real-life MANET testing [19] . An investigation has been carried out on the throughput of the IEEE 802.11 distributed coordination function considering a number of factors, e.g., path loss, multi-path fading [20] . Wu et al [21] analysed the reliability of multihop wireless networks which can suffer from node failure and random channel fading [22] .…”
Section: Background and Related Workmentioning
confidence: 99%
“…If all the STAs in a basic service set (BSS) of the IEEE 802.11 WLAN transmit the packets with constant power (i.e., without power control), then the packet-reception at the AP will naturally hold the capture capability due to the spatial difference among STAs. Some studies have examined the impact of the capture effect on IEEE 802.11 WLANs [12][13][14][15][16]. In [12], the authors presented an analytical model based on Markov chain to demonstrate the probability of successful transmission is increased under capture effect and channel fading.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers conducted a saturation throughput analysis of the IEEE 802.11 DCF under the capture effect [15]. Taking into account the erroneous channel and capture effect, Kumar and Krishnan [16] analyzed the performance of non-saturated traffic in IEEE 802.11 networks.…”
Section: Introductionmentioning
confidence: 99%